2010 24th IEEE International Conference on Advanced Information Networking and Applications 2010
DOI: 10.1109/aina.2010.30
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Execution Costs when Using Globally Distributed Cloud Services

Abstract: Cloud computing is an emerging technology that allows users to utilize on-demand computation, storage, data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 13 publications
0
14
0
4
Order By: Relevance
“…It may be done through distributed processing like using Map-reduce framework of Apache hadoop or Google [34]. In 2010, Pandey et al [35] showed a nonlinear programming model for minimizing execution cost of workflows in cloud using globally distributed cloud storage servers.…”
Section: E Minimizing Computational Costmentioning
confidence: 99%
“…It may be done through distributed processing like using Map-reduce framework of Apache hadoop or Google [34]. In 2010, Pandey et al [35] showed a nonlinear programming model for minimizing execution cost of workflows in cloud using globally distributed cloud storage servers.…”
Section: E Minimizing Computational Costmentioning
confidence: 99%
“…Pandey et al [61] model the cost of an intrusion detection workflow execution on cloud resources using a Non-Linear Programming (NLP) solution. The NLP-model retrieves data partially from multiple data sources based on the cost of transferring data from those resources to a compute resource, so that the total cost of data-transfer and computation cost on that compute resource is minimized.…”
Section: Resource Provisioning In the Cloudmentioning
confidence: 99%
“…It offers on-line processing of regional to global climate change related quantitative RS data products with these multi-source RS data across data centers. The RS data products generated by MDCPS include vegetation related parameters like NDVI 18 and NPP 19 , radiation and hydrothermal flux related parameters like AOD 20 and SM 21 , as well as global ice change and mineral related parameters. The 5-day global synthetic NDVI parameter product in 2014 generated using MODIS 1km data is showed in figure 10.…”
Section: Experiments and Discussionmentioning
confidence: 99%